PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEMUNGKINAN KESULITAN KEUANGAN PADA BURSA EFEK INDONESIA - Indra Hastuti (Jurnal Manajemen Dayasaing, 2014)
Financial distresses have strong relationships with the company’s bankruptcy. The ﬁnancial distress can be predicted by using information contained in the ﬁnancial statements and the company’s corporate governance mechanisms. The purpose of this study is to prove the effect of ownership structure, liquidity ratios, leverage ratios, activity ratios, and the size of the company to possible ﬁnancial distress of manufacturing companies in Indonesia Stock Exchange. Populations of this study are manufacturing companies in Indonesia Stock Exchange, which are published in the ﬁnancial statements from the years 2008-2012,samples of the research  are 156 ﬁnancial. Data analysis uses a logistic regression .The results of this study indicate that managerial ownership signiﬁcantly inﬂuence of ﬁnancial distress. While institutional ownership does not signiﬁcantly inﬂuence of ﬁnancial distress. Liquidity ratios and activity ratios signiﬁcantly inﬂuence of ﬁnancial distress. While the leverage ratio and firm size had no signiﬁcant effect on the ﬁnancial distress. The results can be used for decision making corporate leaders and investors as well as potential investors to always attention Managerial ownership, liquidity ratio, and the ratio of the activity, because these three variables has a contribution in inﬂuencing the potential for ﬁnancial distress.